Nanocoagulation and its influence on the water binding in the composite system of nanosilica— polymethylsiloxane - Krupska, T.V.; Gun’ko, V.M.; Protsak, I.S.; Turov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The formation of a composite system on the basis of equal amounts of hydrophobic porous polymethylsiloxane and hydrophilic nanosilica A-300 is studied. It is shown that, during the formation of the composite system, the specific surface of the material is substantially reduced, which is due to the close contact between the hy drophobic and hydrophilic particles. When water is added to the composite system, in the process of homogenization under the conditions of the metered mechanical load, the effect of nanocoagulation arises as the for mation of nanosized particles of hydrated silica inside the polymethylsiloxane matrix, which is registered on TEM-microphotographs. When measuring the magnitude of the interphase energy of PMS and the composite PMS / A-300 by the method of low-temperature 1H NMR spectroscopy, it is established that the effect of nanocoagulation is manifested in the decrease (in comparison with the initial PMS) of the energy of interaction of water with the surface of the composite obtained under conditions of small mechanical loads and its growth, when high mechanical loads are used.